Prevalence of and risk factors for HBV infection in a metropolitan Southern Italian area: Evidence for the effectiveness of universal Hepatitis B vaccination. Issue 11 (November 2017) - Morisco, Filomena; Stroffolini, Tommaso; Lombardo, Flavia Lucia; Guarino, Maria; Camera, Silvia; Cossiga, Valentina; Donnarumma, Laura; Loperto, Ilaria; Caporaso, Nicola
Abstract: Background: Available data on HBV prevalence in Italy are outdated and assessed with studies conducted in small towns. We aimed to evaluate prevalence of and risk factors for HBV infection in the metropolitan area of Naples, 24 years after the introduction of mass vaccination campaign against Hepatitis B in Italy. Methods: A random systematic sample of the adult general population of Naples was selected from the register of 3 general practitioners in 3 different socio-economic districts. Independent predictors of the likelihood of HBV infection were identified by logistic regression analysis. Results: Among 900 selected subjects, 772 (85.8%) participated in the study. The overall HBsAg and anti-HBc prevalences were 1.7% and 14.4%, respectively. Both markers were more likely detected in the district at low socioeconomic status than in those at medium–high status (p < 0.01). Anti-HBc prevalence linearly increased from 0% in subjects 30 years old or younger to 28.0% in those older than 60 years of age (p < 0.01). At multivariate analysis, age >60 years (OR3.38; 95%CI:1.98–5.74), low socioeconomic district of residence (OR3.26; 95%CI:1.72–6.18), and low educational qualification (OR2.73; 95%CI:1.45–5.16) were independent predictors of anti-HBc positivity. Conclusion: Differences in socioeconomic conditions have played a major role in the past spread of HBV infection in Naples. Hepatitis B vaccination has resulted very effectively in preventing HBV infection, regardless of the district of residence, as none of the subjects in the vaccinated cohorts was exposed to the infection.